Repair of Aneurysmal Arteriovenous Fistulae: A Systematic Review and Meta-analysis - Baláž, Peter; Rokošný, Slavomír; Bafrnec, Jan; Whitley, Adam; O'Neill, Stephen (European journal of vascular and endovascular surgery, 2020)
OBJECTIVE: Aneurysms arising from arteriovenous fistulae are a common finding among dialysed patients and pose a risk of acute bleeding. The aim of this study was to perform a systematic review and meta-analysis evaluating the surgical options for the treatment of aneurysmal arteriovenous fistulae. METHODS: A systematic review and meta-analysis of articles published between January 1973 and March 2019 describing the surgical treatment of arteriovenous fistulae aneurysms. RESULTS: A total of 794 records were identified. After duplicate and low quality studies were removed, 72 full text articles were reviewed and from these 13 were included in the meta-analysis. The total number of patients was 597. Aneurysms were located in the upper arm in 289 (59%) cases and the smallest diameter of a treated aneurysm was 15 mm. The most frequent indication for treatment was bleeding prevention in 513 (86%) cases. Aneurysmorrhaphy was the surgical method of choice in all 13 studies. The pooled primary patency at 12 months was 82% (95% CI 69%-90%, 12 studies, I2 = 84%, p < .01). The 12 month primary patency rates were similar for aneurysmorrhaphy with external prosthetic reinforcement (85%, 95% CI 71%-93%, two studies, I2 = 0%, p = .33) and aneurysmorrhaphy performed using a stapler (74%, 95% CI 61%-83%, four studies, I2 = 0%, p = .48) and without a stapler (82%, 95% CI 60%-94%, six studies, I2 = 92%, p < .01). CONCLUSION: Aneurysmorraphy of arteriovenous fistulae is a procedure with acceptable short and long term results, with a low complication and aneurysm recurrence rate.
Keywords: horní končetina; haemodialysis; arteriovenózní zkrat; Time; pseudoaneurysm; Renal Dialysis; aneurysm; Humans; arteriovenous fistula; Arteriovenous Shunt, Surgical; aneurysma; průchodnost cév; vascular access; lidé; Vascular Patency; čas; Aneurysm; dialýza ledvin; Upper Extremity